Labour and the Culture Wars of Modern Politics. Issue 1 (26th February 2020) - Lawrence, Jon
Abstract: Anyone who attempts to understand and reverse the major defeat suffered by Labour in the December 2019 general election needs first to appreciate why comparisons with the defeats of the 1980s are so unhelpful. In 1983 Labour was all but wiped out across southern England, but held on comfortably across the 'red wall'. By contrast,  in 2019 Labour did well in cities and university towns across the south, and appears to have solved its historic problem with the southern, educated middle class. However, this has been at the expense of alienating working class voters across the country, not just in its former industrial heartlands. But this is not inevitable. A reanalysis of testimony from hundreds of interviews with working people across England from the 1940s onwards allows insights into attitudes and values that are often obscured by survey techniques. Crucially, it points to a broad‐based vernacular liberalism at odds with the culture wars model of a terminal crisis for social democracy.